Travelling to services in the daily urban system of Olomouc - Halás, Marián; Zuskáčová, Veronika (Bulletin of Geography. Socio-economic Series, 2013)
The service sector is quite broad: it includes basic services for the population as well as highly sophisticated services, public as well as commercial services, etc. Commuting to services is one of the fundamental regional processes and together with work commuting it creates an entry basis for the construction of socalled catchment, or nodal regions which should be crucial in the construction of an administrative division of a country. The main objective of this paper is to identify a selected group of spatial interaction in the daily urban system of Olomouc, i.e. in a region dominated by work commuting to the city of Olomouc. More specifically, the paper deals with the interaction of commuting to a wide range of services of non-commercial (social) as well as of commercial character in two hierarchical levels – local and micro-regional. Based on the data obtained by the method of questionnaire research from local leaders (mayors) we analysed the mobility of people to primary and secondary schools, hospitals, shops, culture and sport. As far as the retail network is concerned, the analysis of spatial differentiation of the catchment area to three large department stores was made for villages in Olomouc hinterland. Individual catchment regions for specific services were constructed by a verified method based on commuting flows. Synthetic evaluation contains an identification of so-called complex service regions in the daily urban system of Olomouc. In comparison with our previous studies we tried to describe basic trends in service infrastructure and changes in travelling to services.